Pengaruh Faktor Makro Ekonomi Sebagai Moderator Dalam Hubungan Antara Growth Ratio, Valuation Ratio, dan Rasio Pasar Terhadap Harga Saham: Studi Kasus Di Perusahaan – Perusahaan Yang Terdaftar di BEI - Putri, Mila Kartika Indah; Faisol, Faisol; Kurniawan, Andy (FEB Universitas Maritim Semarang, 2024)
Shares are a very important instrument as a manifestation of company performance. One factor that is considered important in influencing share prices is carrying out financial ratio analysis. The aim of this research is to determine the influence of macroeconomic factors as moderators in the relationship between financial ratios and share prices of companies in the infrastructure sector listed on the IDX for the period 2020 - 2023. This research uses quantitative methods. The sample used in this research includes 21 infrastructure sector companies over a 4 year period, there are 84 observations and the analysis method in this research is panel data regression with STATA software version 14. The results of this research are that price to earnings and earnings per share have a partial effect. significant effect on stock prices, while sales growth, sales growth on stock prices with economic growth as a moderator, price to earnings on stock prices with economic growth as a moderator, earnings per share on stock prices with economic growth as a moderator do not have a significant effect on stock prices. And simultaneously, sales growth, price to earnings and earnings per share on stock prices with economic growth as a moderator have a significant effect.